Factors That Influence New Principal’s Transition Actions and Decisions in Colleges of Education, Ghana - Aggrey-Fynn, Caroline (International Journal of Scientific Research and Management (IJSRM), 2019)
This study was to investigate the factors that influence new college of education principals during transition. The study employed descriptive research design and data was collected from ten respondents from public colleges in Ghana. The findings showed that actions and decisions of the principals during their transitions were influenced by four categories of factors which were: internal factors, internal individuals, external factors and external individuals. However, the actions and decisions were influenced more by internal and external factors and individuals rather than the principals’ personal beliefs and philosophies. Practically, the findings of the study opens up the decision influencing factors in transition and serves as a guide for college leaders and other school leaders in transition. The study recommended that new principals should pay attention to internal and external factors and individuals as they set transition goals, priorities and actions to help align interests and reduce resistance to any change situation that may result from the transition.